Clozapine-Induced Myocarditis or Acute Coronary Syndrome? Optical Coherence Tomography to the Rescue. (19th July 2018) - Dina, Ayodeji; Barlis, Peter; van Gaal, William
Abstract : Chest pain and troponin elevation may be due to an acute coronary syndrome, myocarditis, acute cardiomyopathy, or other less common conditions. Management differs depending on the aetiology, and the pathophysiologic diagnosis has direct implications on treatment and patient outcomes. History and clinical examination is supplemented by selected investigations including the electrocardiogram, chest X-ray, echocardiography, coronary angiography, and even myocardial perfusion scintigraphy or cardiac magnetic resonance imaging. Intravascular imaging can provide important insights into the underlying mechanism of acute coronary syndromes, especially when angiography is ambiguous.